Delayed Neuropathologic Changes After Carbon Monoxide Intoxication Two Case Reports - Turan, Arzu Akçay; Pakiş, Işıl; Arıcan, Nadir; Karayel, Ferah; Şam, Bülent; Kavas, Gamze; Öz, Büge (The Bulletin of Legal Medicine, 2003)
Carbon monoxide (CO) is a common environmental toxin and a leading cause of lethal poisoning around the world. Systemic and neurological changes related to CO intoxication occurs due to diffuse hypoxia and direct toxicity of the gas. 70 and 35 years old females, exposed accidentally to CO, 18 days and 8 months before death have analyzed. Our first case was 70 year old female who had been exposed to CO at her house and found in a state of cardiopulmonary arrest. After admission, she was resuscitated and underwent artificial ventilation in a comatose state and died after 18 days. Second case was 35 years old female with a history of CO intoxication, 8 months before. After 45 days of hospitalisation period, cooperation problems and movement disorders eventually developed. She died due to injuries caused by falling from a height. On macroscopic examination, first case had diffuse petechial bleeding on basal ganglia and bilateral necrosis of globus pallidus. We found diffuse cortical atrophy and pale regions on basal ganglia, hyppocampus, cerebellum and cerebral white matter. On microscopic examination, we found bilateral subacute infarction of globus pallidus, myelin degeneration and astrogliosis in sentrum semiovale of first case. The second case had neuronal loss at cerebral cortex, hyppocampus, internal granular cell and purkinje cell layer of cerebellum, myelin pallor, white matter injury and astrogliosis around basal ganglia. Grey and white matter lesions of both cases are common lesions of CO intoxication. In the second case, particularly white matter lesions can explain neurologic sequeles. Neurologic or neuropsychological disorders can cause serious trauma on late phase of CO intoxication. However, although trauma alone is considered as the cause of death as seen as in second case, contribution of neurophysiologic and neuropathologic changes due to CO intoxication on the process should not be ignored. Key words: Carbon monoxide, intoxication, brain, neuropsychiatric syndrome